Molecular cloning of Erwinia chrysanthemi pectinase and cellulase structural genes - Kotoujansky, Alain (1985)
Erwinia chrysanthemi 3937 secretes four major pectate lyase isoenzymes (PL, EC 4.2.2.2) and one endocellulase (Cx, EC 3.2.1.4). A genomic library of this strain was constructed in the Lambda L47-1 vector, and screened for the presence of PL and Cx on pectate and caboxymethylcellulose agar. Among the seven Cx-positive phage clones, three were shown to encode an enzyme of the same mol. wt. as the one found in the culture supernatant of strain 3937. The 34 PL-positive phage clones were analyzed by electrofocusing and could, according to the PL they produced, be arranged in five classes. Phages from three classes produced three different single PL, named PLb, c and d. No common fragment was evidenced between the inserts of the phages of these three classes. This demonstrated that, in strain 3937, PLb, C, and d were encoded by three different genes called pelB, C, and D. Furthermore, our results suggest the existence of two additional genes encoding PLa and e. In addition, a pectin methylesterase gene was found closely linked to pelD.